A molecular dynamics simulation on the effect of different parameters on thermal resistance of graphene-argon interface. Issue 4 (4th March 2017) - Amani, A.; Karimian, S. M. H.; Seyednia, M.
Abstract: Molecular dynamics simulations of argon molecules confined between two parallel graphene sheets are carried out to investigate the parameters affecting heat transfer and thermal properties. These parameters include wall–fluid interaction strength, fluid density and wall temperature. For constant wall temperature simulations, we show that the first two parameters have influence on near-wall fluid density. As a result, the heat transfer at wall–fluid interfaces and thus through argon molecules across the domain will change. Also, we demonstrate that variations in wall temperature rarely affects the density profiles of argon molecules next to the walls. Therefore, in these cases, the variations in thermal resistance at the interface is most dominantly due to wall temperature itself. To analyse the results, the density and temperature profiles and also other parameters including heat flux and temperature gradient of bulk of argon molecules, Kapitza length and argon thermal conductivity are considered. The Kapitza length describes thermal resistance at liquid–solid interface. According to the results, increasing wall–fluid interaction strength leads to greater molecular aggregation of argon molecules near the walls and, consequently, decreasing the Kapitza length. Furthermore, higher fluid density leads to greater thermal resistance at wall–fluid interactions and therefore greater temperature jumps are observed in temperature profiles.